Collective responses to regional problems : the case of Latin America and the Caribbean - Kaysen, Carl ed. (Committee on International Security Studies CambridgeUS, 1994)
Examines the record of international action to cope with regional problems as well as the policy implications of the recent shift toward greater democracy and the changing relationships among Latin American countries and the United States.